Andrological findings in infertile men with two (biallelic) CFTR mutations: results of a multicentre study in Germany and Austria comprising 71 patients. Issue 3 (29th December 2020) - Rudnik-Schöneborn, S; Messner, M; Vockel, M; Wirleitner, B; Pinggera, G -M; Witsch-Baumgartner, M; Murtinger, M; Kliesch, S; Swoboda, M; Sänger, N; Zschocke, J; Tüttelmann, F
Abstract: STUDY QUESTION: When should cystic fibrosis transmembrane conductance regulator ( CFTR ) mutation analysis be recommended in infertile men based on andrological findings? SUMMARY ANSWER: CFTR mutation analysis is recommended in all men with unexplained azoospermia in the presence of normal gonadotropin levels. WHAT IS KNOWN ALREADY: While 80–97% of men with congenital bilateral absence of the vas deferens (CBAVD) are thought to carry CFTR mutations, there is uncertainty about the spectrum of clinical and andrological abnormalities in infertile men with bilallelic CFTR mutations. This information is relevant for evidence-based recommendations to couples requesting assisted reproduction. STUDY DESIGN, SIZE, DURATION: We studied the andrological findings of patients with two CFTR mutations who were examined in one of the cooperating fertility centres in Germany and Austria. In the period of January till July 2019, the completed and anonymized data sheets of 78 adult male patients were returned to and analysed by the project leader at the Institute of Human Genetics in Innsbruck, Austria. PARTICIPANTS/MATERIALS, SETTING, METHODS: Minimum study entry criteria were the presence of two (biallelic) CFTR mutations and results of at least one semen analysis. Andrological assessments were undertaken by standardized data sheets and compared with normal reference values. Seventy-one patients were eligible for the study (n = 30, 42% from Germany, n = 26, 37% from Austria, n = 15, 21% other nations). MAIN RESULTS AND THE ROLE OF CHANCE: Gonadotropin levels (FSH, LH) were normal, 22% of patients had reduced testosterone values. Mean right testis volume was 23.38 ml (SD 8.77), mean left testis volume was 22.59 ml (SD 8.68) and thereby statistically increased compared to normal ( P < 0.01). although the means remained in the reference range of 12–25 ml. Semen analysis revealed azoospermia in 70 of 71 (99%) patients and severe oligozoospermia <0.1 × 10 6 /ml in one patient. Four semen parameters, i.e. ejaculate volume, pH, α-glucosidase and fructose values, were significantly reduced ( P < 0.01). Only 18% of patients had a palpatory and sonographically diagnosed CBAVD, while in 31% the diagnosis of CBAVD was uncertain, in 12% patients, the vas deferens was present but hypoplastic, and in 39% the vas deferens was normally present bilaterally. Seminal vesicles were not detectable in 37% and only unilaterally present in 37% of patients. Apart from total testes volume, clinical findings were similar in patients with two confirmed pathogenic CFTR mutations (Group I) compared with patients who carried one pathogenic mutation and one CFTR variant of unknown significance (Group II). LIMITATIONS, REASONS FOR CAUTION: We could not formally confirm the in trans position of genetic variants in most patients as no family members were available for segregation studies. Nonetheless, considering that most mutations in our study have been previously described without other rare variants in cis, and in view of the compatible andrological phenotype, it is reasonable to assume that the biallelic genotypes are correct. WIDER IMPLICATIONS OF THE FINDINGS: Our study reveals that CFTR mutation analysis has a broader indication than just the absence of the vas deferens. We recommend to completely sequence the CFTR gene if there is a suspicion of obstructive azoospermia, and to extend this analysis to all patients with unexplained azoospermia in the presence of normal gonadotropin levels. STUDY FUNDING/COMPETING INTEREST(S): German Research Foundation Clinical Research Unit 'Male Germ Cells: from Genes to Function' (DFG CRU326, grants to F.T.). There are no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.